2011
DOI: 10.4067/s0718-95162011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of grazing on the soil properties and C and N storage in relation to biomass allocation in an alpine meadow

Abstract: Livestock grazing is one of the most important factors influencing the above-ground community composition and structure in a natural grassland ecosystem. Different grazing intensities also have the potential to alter soil C and N storage substantially in grasslands. We conducted a field community study and soil analyses to determine the effects of different grazing intensities on the above-ground community and soil properties in an alpine meadow on the Tibetan Plateau. Our results showed the following: (i) the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 29 publications
4
28
0
Order By: Relevance
“…There are well-documented positive effects of woody cover on SOC (Tighe et al, 2009;Li et al, 2011;Simón et al, 2013;Pulido-Fernández et al, 2013;Kurgat et al, 2014) and associated benefits of increased infiltration and soil stability (Daryanto & Elderidge, 2010). Kurgat et al (2014) reported 0·41% higher levels of SOC under shrubs compared with bare ground, and Belay & Kebede (2010) found 0·38 to 0·23% perennial grasses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are well-documented positive effects of woody cover on SOC (Tighe et al, 2009;Li et al, 2011;Simón et al, 2013;Pulido-Fernández et al, 2013;Kurgat et al, 2014) and associated benefits of increased infiltration and soil stability (Daryanto & Elderidge, 2010). Kurgat et al (2014) reported 0·41% higher levels of SOC under shrubs compared with bare ground, and Belay & Kebede (2010) found 0·38 to 0·23% perennial grasses.…”
Section: Discussionmentioning
confidence: 99%
“…Overgrazing is recognized as an important factor in rangeland degradation, but there is a lack of unanimity for the effects of livestock grazing on soil C. Some recent studies show a decrease (Su et al, 2004;Zuo et al, 2008;Mofidi et al, 2012), no significant change (Sanjari et al, 2008;Allen et al, 2013;Lu et al, 2015) or an increase in soil C (Reeder & Schuman, 2002;Li et al, 2011). These inconsistencies are due to differences in plant species composition (Piñeiro et al, 2010), the legacy of previous management and interactions between these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Livestock overgrazing is one of the most important factor that results in grassland degradation, soil erosion and nutrient losses (Wei et al 2011). Due to overgrazing, the natural vegetation in the northern highlands of Ethiopia has virtually disappeared, leaving degraded communal grazing lands with irregularly spaced trees and shrubs and vast areas of bare lands devoid of vegetation (Nedessa et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, some studies showed that the grazing intensity and SOC had a negative correlation (Derner et al, 1997;Bagchi and Ritchie, 2010;Wu et al, 2009) or no relationship (Milchunas and Lauenroth, 1993;Holt, 1997). By contrast, many other studies showed that grazing can increase the SOC (Schuman et al, 1999;Wienhold et al, 2001;Li et al, 2011). This is partly because moderate grazing can increase the grassland belowground biomass, which is beneficial for the accumulation of SOC (López-Mársico et al, 2015;Hafner et al, 2012).…”
Section: Effects Of Grazing Intensity On Biomass and Socmentioning
confidence: 99%